2010
DOI: 10.1107/s0907444910002702
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent macromolecular X-ray crystallography

Abstract: X-ray crystallography provides structural details of biological macromolecules. Whereas routine data are collected close to 100 K in order to mitigate radiation damage, more exotic temperature-controlled experiments in a broader temperature range from 15 K to room temperature can provide both dynamical and structural insights. Here, the dynamical behaviour of crystalline macromolecules and their surrounding solvent as a function of cryo-temperature is reviewed. Experimental strategies of kinetic crystallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 127 publications
(170 reference statements)
2
88
0
Order By: Relevance
“…They may be particularly useful in studies of the protein glass transition, in mechanistic studies of protein function and in the developing field of kinetic crystallography (Bourgeois & Royant, 2005;Colletier et al, 2008;Weik & Colletier, 2010), in which temperature can be used as a parameter to control reaction rates within crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may be particularly useful in studies of the protein glass transition, in mechanistic studies of protein function and in the developing field of kinetic crystallography (Bourgeois & Royant, 2005;Colletier et al, 2008;Weik & Colletier, 2010), in which temperature can be used as a parameter to control reaction rates within crystals.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, radiation damage at temperatures spanning the full range T = 300-100 K remains a major issue in structural biology (Weik & Colletier, 2010). The mechanisms by which X-rays degrade diffraction quality throughout this temperature range remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these small conformational perturbations, the dynamic characteristics of proteins in crystals are exquisitely sensitive to temperature (11,12). After accounting for static structural differences between molecules, model errors, and crystal lattice defects in myoglobin crystals, Frauenfelder and Petsko demonstrated widespread temperature-dependent decreases in the harmonic atomic vibrations measured by B-factors.…”
mentioning
confidence: 99%
“…A landmark study of crystalline ribonuclease A (RNaseA) by Tilton, Petsko, and coworkers revealed diverse temperature-dependent changes in the average structure, ranging from shrinkage at low temperatures to increased loop disorder at 47°C (9). A recent analysis comparing 15 room-temperature and cryogenic crystal structures documented that cryocooling generally increases lattice contacts and reduces protein volumes but causes only small changes in crystallographic models (10).In contrast to these small conformational perturbations, the dynamic characteristics of proteins in crystals are exquisitely sensitive to temperature (11,12). After accounting for static structural differences between molecules, model errors, and crystal lattice defects in myoglobin crystals, Frauenfelder and Petsko demonstrated widespread temperature-dependent decreases in the harmonic atomic vibrations measured by B-factors.…”
mentioning
confidence: 99%
“…Typically, X-ray crystallographic data are measured from crystals maintained at 100 K in order to immobilize X-raygenerated free radicals and damaged protein and minimize radiation damage, leading an increase in crystal lifetime of up to two orders of magnitude relative to RT (Southworth-Davies et al, 2007). Between RT and 100 K, protein crystals undergo at least one and possibly several temperature-dependent transitions (Weik & Colletier, 2010;Lewandowski et al, 2015;Ringe & Petsko, 2003;Keedy et al, 2015). Notably, anharmonic macromolecular motions resume above the glass transition that occurs in the range 180-220 K, where solvent viscosity is greatly reduced.…”
Section: Introductionmentioning
confidence: 99%